Experimental and theoretical study on the remarkable influence of protecting groups on the selectivity of addition of amines to vinyl sulfone-modified hex-2-enopyranosides - Bhattacharya, Rahul; Kesharwani, Manoj K.; Manna, Chinmoy; Ganguly, Bishwajit; Suresh, Cheravakattu G.; Pathak, Tanmaya (Journal of Organic Chemistry, 2010)
Although phenylmethylene-protected vinyl sulfone-modified carbohydrate 2 alpha reacts with both primary and secondary amines in Michael fashion to afford aminated products, only primary amines react with the dibenzyl-protected 3 alpha, 6-O-trityl-protected 4 alpha, and unprotected 5 alpha, highlighting for the first time the remarkable influence of protecting, groups on the reaction patterns of vinyl sulfone-modified carbohydrates. The quantum chemical calculations suggest that the Michael addition of amines and proton transfer to vinyl sulfone-modified carbohydrates 2 alpha and 5 alpha are possible via relay process in a concerted mechanism. These calculations reveal that the addition of primary amines to vinyl sulfone-modified carbohydrate is preferential due to the low activation energy barriers, whereas the addition of secondary amines has relatively higher activation energy barriers. The theoretical conclusions are in line with the experimental observations.

Borazine as a sensor for fluoride ion: a computational and experimental study - Kesharwani, Manoj K.; Suresh, Moorthy; Das, Amitava; Ganguly, Bishwajit (Tetrahedron Letters, 2011)
The computational and experimental studies have revealed that even simple molecule like borazine can act as a sensor for fluoride ions. This study further reported the various binding modes of analytes using quantum chemical calculations and the nature of such interactions have been examined using electron density surface analysis. Total charge transfer analysis (qCT) correlates well with the binding affinities of analytes with the borazine receptor.

Folding and unfolding movements in a [2]pseudorotaxane - Suresh, Moorthy; Mandal, Amal Kumar; Kesharwani, Manoj K.; Adarsh, N. N.; Ganguly, Bishwajit; Kanaparthi, Ravi Kumar; Samanta, Anunay; Das, Amitava (Journal of Organic Chemistry, 2011)
A new dibenzo[24]crown-8 derivative (1) was synthesized and functionalized with aromatic moieties such as naphthalene and coumarin units. These two fluorophores are known to form an effective FRET (Forster resonance energy transfer) pair, and this formed the basis for the design of this host crown ether derivative. Results of the steady-state and time-resolved fluorescence studies confirmed the resonance energy transfer between the donor naphthalene moiety and acceptor coumarin fragment, while NMR spectra and computational studies support a folded conformation for the uncomplexed crown ether 1. This was found to form an inclusion complex, a [2]pseudorotaxane type with imidazolium ion derivatives as the guest molecules with varying alkyl chain lengths ([C4mim]+ or [C10mim]+). The host crown ether (1) tends to adopt an open conformation on formation of the interwoven inclusion complex (1·[C4mim]+ or 1·[C10mim]+). This change in conformation, from the folded to a open one, was predicted by computational as well as 1H NMR studies and was confirmed by single crystal X-ray structure for one (1·[C4mim]+) of the two inclusion complexes. The increase in the effective distance between the naphthalene and coumarin moieties in the open conformation of these inclusion complexes was also supported by the decrease in the effective FRET process that was operational between naphthalene and coumarin moieties in the free molecule (1). Importantly, this inclusion complex formation was found to be reversible, and in the presence of a stronger base/polar solvent, such as triethyl amine/DMSO, the deprotonation/effective solvation of the cationic imidizolium ions ([C4mim]+ or [C10mim]+) resulted in decomplexation or dethreading with restoration of the original emission spectra for 1, which signifies the subsequent increase in the FRET process. Thus we could demonstrate that a molecular folding-unfolding type of movement in the crown ether derivative could be induced by chemical input as an imidazolium ion.

Receptor design and extraction of inorganic fluoride ion from aqueous medium - Das, Priyadip; Mandal, Amal Kumar; Kesharwani, Manoj K.; Suresh, Eringathodi; Ganguly, Bishwajit; Das, Amitava (Chemical Communications, 2011)
A receptor with acidic methylene hydrogens is found to act as an efficient binding mode for F−. This reagent could as well be used for selective and quantitative extraction of F− from the aqueous solution of NaF and sea water.

ZnII-2,2?:6?,2?-terpyridine-based complex as fluorescent chemosensor for PPi, AMP and ADP - Das, Priyadip; Ghosh, Amrita; Kesharwani, Manoj K.; Ramu, Vadde; Ganguly, Bishwajit; Das, Amitava (Europian Journal of Inorganic Chemistry, 2011)
A new ZnII–2,2′:6′,2″-terpyridine complex, derivatized with a coumarin moiety (L1Zn), acts as a fluorescent chemosensor for different biologically important phosphates like PPi, AMP and ADP in mixed aqueous media. Depending on the proportion of the aqueous fraction present in the solvent mixture, L1Zn shows a preference for different phosphate moieties at physiological pH. In an aqueous acetonitrile (2:3, v/v) medium this reagent shows a preference for AMP as compared to ADP, ATP and PPi. The binding affinities of L1Zn with different phosphate ions and associated shifts in the electronic spectra were rationalized by DFT calculations. Such an example of a receptor that is selective for AMP under physiological conditions is rare in the literature.

Alternative approach: a highly selective dual responding fluoride sensor having active methylene group as binding site - Das, Priyadip; Kesharwani, Manoj K.; Mandal, Amal K.; Suresh, Eringathodi; Ganguly, Bishwajit; Das, Amitava (Org Biomol Chem., 2012)
A newly designed phosphonium derivative (L) having active methylene functionality, shows unusual preference towards F− over all other anions. The binding process through C–H⋯F− hydrogen bond formation was probed by monitoring the changes in either electronic or luminescence spectra. Changes in both cases are significant enough to allow visual detection. The loss of molecular flexibility of L on forming L·F− effectively interrupts the non-radiative deactivation pathway and accounts for the observed switch on fluorescence response. The results of the time-resolved emission studies for L and L·F− using a time-correlated single photon counting technique further corroborate this presumption. The excellent preference of L towards F− is attributed to an efficient hydrogen bonding interaction between the strongly polarized methylene protons and F−, which delineates the subtle difference in the affinity among other competing anionic analytes like CN−, H2PO4−, CH3CO2−, etc. The relative affinities of various anions and the preferential binding of F− to reagent L are also rationalized using computational studies.

New chemodosimetric reagents as ratiometric probes for cysteine and homocysteine and possible detection in living cells and in blood plasma - Das, Priyadip; Mandal, Amal Kumar; Chandar, Nellore Bhanu; Baidya, Mithu; Bhatt, Harshad B.; Ganguly, Bishwajit; Ghosh, Sudip K.; Das, Amitava (Chemistry a European Journal, 2012)
In this work, we have rationally designed and synthesized two new reagents (L1 and L2), each bearing a pendant aldehyde functionality. This aldehyde group can take part in cyclization reactions with β- or γ-amino thiols to yield the corresponding thiazolidine and thiazinane derivatives, respectively. The intramolecular charge-transfer (ICT) bands of these thiazolidine and thiazinane derivatives are distinctly different from those of the molecular probes (L1 and L2). Such changes could serve as a potential platform for using L1 and L2 as new colorimetric/fluorogenic as well as ratiometric sensors for cysteine (Cys) and homocysteine (Hcy) under physiological conditions. Both reagents proved to be specific towards Cys and Hcy even in the presence of various amino acids, glucose, and DNA. Importantly, these two chemodosimetric reagents could be used for the quantitative detection of Cys present in blood plasma by using a pre-column HPLC technique. Such examples are not common in contemporary literature. MTT assay studies have revealed that these probes have low cytotoxicity. Confocal laser scanning micrographs of cells demonstrated that these probes could penetrate cell membranes and could be used to detect intracellular Cys/Hcy present within living cells. Thus, the results presented in this article not only demonstrate the efficiency and specificity of two ratiometric chemodosimeter molecules for the quantitative detection of Cys and Hcy, but also provide a strategy for developing reagents for analysis of these vital amino acids in biological samples.
Keywords: charge transfer; chemodosimetric detection; cysteine/ homocysteine sensors; fluorescent probes; imaging agents; ratiometric probes

Photosensitization of nanoparticulate TiO2 using a Re(I)-polypyridyl complex: studies on interfacial electron transfer in the ultrafast time domain - Kar, Prasenjit; Banerjee, Tanmay; Verma, Sandeep; Sen, Anik; Das, Amitava; Ganguly, Bishwajit; Ghosh, Hirendra N. (Physical Chemistry Chemical Physics, 2012)
We have synthesized a new photoactive rhenium(I)-complex having a pendant catechol functionality [Re(CO)3Cl(L)] (1) (L is 4-[2-(4′-methyl-2,2′-bipyridinyl-4-yl)vinyl]benzene-1,2-diol) for studying the dynamics of the interfacial electron transfer between nanoparticulate TiO2 and the photoexcited states of this Re(I)-complex using femtosecond transient absorption spectroscopy. Our steady state absorption studies revealed that complex 1 can bind strongly to TiO2 surfaces through the catechol functionality with the formation of a charge transfer (CT) complex, which has been confirmed by the appearance of a new red-shifted CT band. The longer wavelength absorption band for 1, bound to TiO2 through the proposed catecholate functionality, could also be explained based on the DFT calculations. Dynamics of the interfacial electron transfer between 1 and TiO2 nanoparticles was investigated by studying kinetics at various wavelengths in the visible and near infrared regions. Electron injection into the conduction band of the nanoparticulate TiO2 was confirmed by detection of the conduction band electron in TiO2 (Image ID:c2cp24105f-t1.gif) and the cation radical of the adsorbed dye (1˙+) in real time as monitored by transient absorption spectroscopy. A single exponential and pulse-width limited (<100 fs) electron injection was observed. Back electron transfer dynamics was determined by monitoring the decay kinetics of 1˙+ and Image ID:c2cp24105f-t2.gif.

Ratiometric detection of Cr3+ and Hg2+ by a naphthalimide-rhodamine based fluorescent probe - Mahato, Prasenjit; Saha, Sukdeb; Suresh, E.; Liddo, Rosa Di; Parnigotto, Pier Paolo; Conconi, Maria Teresa; Kesharwani, Manoj K.; Ganguly, Bishwajit; Das, Amitava (Inorganic Chemistry, 2012)
Newly synthesized rhodamine derivatives, L1 and L2, are found to bind specifically to Hg2+ or Cr3+ in presence of large excess of other competing ions with associated changes in their optical and fluorescence spectral behavior. These spectral changes are significant enough in the visible region of the spectrum and thus, allow the visual detection. For L1, the detection limit is even lower than the permissible [Cr3+] or [Hg2+] in drinking water as per standard U.S. EPA norms; while the receptor, L2 could be used as a ratiometric sensor for detection of Cr3+ and Hg2+ based on the resonance energy transfer (RET) process involving the donor naphthalimide and the acceptor Cr3+/Hg2+-bound xanthene fragment. Studies reveal that these two reagents could be used for recognition and sensing of Hg2+/Cr3+. Further, confocal laser microscopic studies confirmed that the reagent L2 could also be used as an imaging probe for detection of uptake of these ions in A431 cells.

Molecular interactions, proton exchange, and photoinduced processes prompted by an inclusion process and a [2]pseudorotaxane formation - Mandal, Amal Kumar; Suresh, Moorthy; Kesharwani, Manoj K.; Gangopadhyay, Monalisa; Agrawal, Manoj; Boricha, Vinod P.; Ganguly, Bishwajit; Das, Amitava (Journal of Organic Chemistry, 2013)
Appropriate design of the host and guest components allows formation of a novel [2]pseudorotaxane complex with an interrupted photoinduced electron transfer (PET)-coupled fluorescence resonance energy transfer (FRET) response. This is the first example of an inclusion complex with NO6-based azacrown ether as the host unit (H). Different guest molecules (G1, G2, G3, and G4) with varying stopper size are used for the studies. Unlike G1, G2, and G3, G4 with a relatively bulkier stopper fails to form a [2]pseudorotaxane complex. Isothermal titration microcaloiimetry measurements reveal a systematic increase in the association constant for H.G1, H.G2, and H.G3 with a change in the stopper size. Thermodynamic data suggest that the formation of H.G1/H.G2/H.G3 is exclusively driven by a large positive entropic gain (T Delta S = 19.69/26.80/21.81 kJ.mol(-1)), while the enthalpy change is slightly negative for H.G1/H.G3 (-2.61/-1.97 kJ.mol(-1)) and slightly positive for H.G2 (Delta H = 5.98 kJ.mol(-1)). For these three inclusion complexes, an interrupted PET-coupled FRET response is observed with varying efficiency, which is attributed to the subtle differences in acidity of the NH2+ unit of the guest molecules and thus the proton exchange ability between the host and respective guest. This is substantiated by the results of the computational studies.

New receptor with a FRET based fluorescence response for selective recognition of fumaric and maleic acids in aqueous medium - Reddy, Upendar G.; Lo, Rabindranath; Roy, Sovan; Banerjee, Tanmay; Ganguly, Bishwajit; Das, Amitava (Chemical Communications, 2013)
Preferential binding of a new reagent to fumaric acid could be utilized for its estimation in aqueous medium and in commercial fruit juice.

Role of metal ion in specific recognition of pyrophosphate ion under physiological conditions and hydrolysis of the phosphoester linkage by alkaline phosphatase - Das, Priyadip; Chandar, Nellore Bhanu; Chourey, Shishir; Agarwalla, Hridesh; Ganguly, Bishwajit; Das, Amitava (Inorganic Chemistry, 2013)
Complexes synthesized from Zn(II), Cu(II), and Cd(II), using a dipicolyl amine derivative (L), showed unique specificity toward pyrophosphate ion (PPi or P4O74-) among all other common anionic analytes, including different biologically significant phosphate ion (PO43-, H2PO42-) or phosphate-ion-based nucleotides, such as AMP, ADP, ATP, and CTP. However, the relative affinities of PPi toward these three metal complexes were found to vary and follow the order K-a(L.Zn-PPi) > are given in units of (L.Cu-PPi)(a) >= K-a(L.Cd-PPi). Luminescence responses of the receptor L were substantial on binding to Zn2+ and Cd2+, while relatively a much smaller luminescence response was observed in the presence of Cu2+. Luminescence responses of L.M-PPi (M is Zn2+, Cd2+, and Cu2+) were further modified on binding to the PPi ion. This could be utilized for quantitative detection of PPi in physiological condition as well as for developing a real time ``turn-on'' (for L.Zn and L.Cu) and ``turn-off'' (for L.Cd) fluorescence assay for evaluating the enzymatic activity of alkaline phosphatase (ALP). Experimental results revealed how the subtle differences in the binding affinities between PPi and M in L.M (M is Zn2+, Cd2+, and Cu2+), could influence the cleavage of the phosphoester linkage in PPi by ALP. The DFT calculations further revealed that the hydrolytic cleavage of the metal ion coordinated phosphoester bond is kinetically faster than that for free PPi and thus, rationalized the observed difference in the cleavage of the phosphoester bond by an important mammalian enzyme such as ALP in the presence of different metal complexes.

Design of efficient metal-free organic dyes having an azacyclazine scaffold as the donor fragment for dye-sensitized solar cells - Biswas, Abul Kalam; Barik, Sunirmal; Sen, Anik; Das, Amitava; Ganguly, Bishwajit (Journal of Physical Chemistry C, 2014)
The energy conversion efficiency of dye-sensitized solar cells derived from organic dye molecules has seen immense interest recently. In this work, we report a series of organic donor molecules with enhanced energy conversion efficiency using ?-spacers and cyanoacrylic acid as an anchoring group (2-6). Density functional theory (DFT) and time-dependent DFT calculations of these molecules have been performed to examine their electronic structures and absorption spectra before and after binding to the semiconductor titanium dioxide surface. The computational results suggest that dyes 4 and 6 have a larger driving force (Delta G(inject) = -1.66 and -1.80 eV, respectively) and light-harvesting efficiency (LHE = 0.99) in the series of donor molecules studied. Thus, these dyes should possess a larger short-circuit photocurrent density (J(sc)) compared to the other examined dyes. The reported Delta G(inject) (-1.62 eV) and LHE (0.98) for compound 1, calculated with the same level of theory, were lower than those of the designed 4 and 6 dyes. Furthermore, the DFT calculations showed that the open-circuit photovoltage (V-oc) is improved with the vertical dipole moment and number of photoinjected electrons for 4 and 6. Dyes 4 and 6 are expected to exhibit high solar-energy-to-electricity conversion.

Hydrogen bonding interaction between active methylene hydrogen atoms and an anion as a binding motif for anion recognition: experimental studies and theoretical rationalization - Agarwalla, Hridesh; Jana, Kalyanashis; Maity, Arunava; Kesharwani, Manoj K.; Ganguly, Bishwajit; Das, Amitava (Journal of Physical Chemistry A, 2014)
Two new reagents, having similar spatial arrangements for hydrogen atoms of the active methylene functionalities, were synthesized and interactions of such reagents with different anionic analytes were studied using electronic spectroscopy as well as by using 1H and 31P NMR spectroscopic methods. Experimental studies revealed that these two reagents showed preference for binding to F– and OAc–. Detailed theoretical studies along with the above-mentioned spectroscopic studies were carried out to understand the contribution of the positively charged phosphonium ion, along with methylene functionality, in achieving the observed preference of these two receptors for binding to F– and OAc–. Observed differences in the binding affinities of these two reagents toward fluoride and acetate ions also reflected the role of acidity of such methylene hydrogen atoms in controlling the efficiencies of the hydrogen bonding in anion–Hmethylene interactions. Hydrogen bonding interactions at lower concentrations of these two anionic analytes and deprotonation equilibrium at higher concentration were observed with associated electronic spectral changes as well as visually detectable change in solution color, an observation that is generally common for other strong hydrogen bond donor functionalities like urea and thiourea. DFT calculations performed with the M06/6-31+G**//M05-2X/6-31G* level of theory showed that F– binds more strongly than OAc– with the reagent molecules. The deprotonation of methylene hydrogen atom of receptors with F– ion was observed computationally. The metal complex as reagent showed even stronger binding energies with these analytes, which corroborated the experimental results.

New Ru(II)/Os(II)-polypyridyl complexes for coupling to TiO2 surfaces through acetylacetone functionality and studies on interfacial electron-transfer dynamics - Banerjee, Tanmay; Biswas, Abul Kalam; Sahu, Tuhin Subhra; Ganguly, Bishwajit; Das, Amitava; Ghosh, Hirendra Nath (Dalton Transactions, 2014)
New Ru(II)- and Os(II)-polypyridyl complexes have been synthesized with pendant acetylacetone (acac) functionality for anchoring on nanoparticulate TiO2 surfaces with a goal of developing an alternate sensitizer that could be utilized for designing an efficient dye-sensitized solar cell (DSSC). Time-resolved transient absorption spectroscopic studies in the femtosecond time domain have been carried out. The charge recombination rates are observed to be very slow, compared with those for strongly coupled dye molecules having catechol as the anchoring functionality. The results of such studies reveal that electron-injection rates from the metal complex-based LUMO to the conduction band of TiO2 are faster than one would expect for an analogous complex in which the chromophoric core and the anchoring moiety are separated with multiple saturated C-C linkages. Such an observation is rationalized based on computational studies, and a relatively smaller spatial distance between the dye LUMO and the TiO2 surface accounted for this. Results of this study are compared with those for analogous complexes having a gem-dicarboxy group as the anchoring functionality for covalent binding to the TiO2 surface to compare the role of binding functionalities on electron-transfer dynamics.

Superior grafting and state-of-the-art interfacial electron transfer rates for newly designed geminal dicarboxylate bound ruthenium(II)- and osmium(II)-polypyridyl dyes on TiO2 nanosurface - Banerjee, Tanmay; Biswas, Abul Kalam; Reddy, Upendar G.; Sahu, Tuhin Subhra; Das, Amitava; Ganguly, Bishwajit; Ghosh, Hirendra Nath (Journal of Physical Chemistry C, 2014)
Two new Ru(II)-/Os(II)-polypyridyl based sensitizer dyes with geminal dicarboxylic acid group as the binding unit for superior grafting of the dye to TiO2 have been designed and synthesized. Steady-state photochemical studies of the two sensitizer dyes in presence of TiO2 in water confirm strong binding of the dyes to TiO2. Femtosecond transient absorption studies of these newly synthesized dyes on TiO2 nanosurface have been carried out in water and the results have been compared with those for the corresponding 4,4'-dicarboxy-2,2'-bipyridine analogues of the dyes. While the charge recombination rates are considerably slower, interestingly, the electron injection rates are very fast for multiple saturated C-C linkages present between the chromophoric core and the anchoring moiety. The origin and the consequences of such profound effects on the ultrafast interfacial dynamics are discussed. This is the first report on the ultrafast transient absorption studies of dyes with geminal dicarboxylic acid binding groups, which we believe will add significantly to the present research efforts toward the development of robust and efficient dyes for use in dye solar applications.

Can silicon substituted metal-free organic dyes achieve better efficiency compared to silicon free organic dyes? a computational study - Biswas, Abul Kalam; Das, Amitava; Ganguly, Bishwajit (Physical Chemistry Chemical Physics, 2015)
The power conversion efficiency of metal-free organic dyes in dye-sensitized solar cells (DSSCs) is now comparable to ruthenium-based polypyridyl and zinc-based porphyrin dyes. We have computationally investigated the structural, electronic and optical properties of a series of metal free organic dyes and their corresponding silicon substituted dyes. The DFT and TD-DFT calculations revealed that silicon substituted organic dyes have higher efficiency than the corresponding silicon free organic dyes. The computational results showed that the presence of silole units as a spacer group can significantly affect the performance of DSSCs compared to typically using thiophene as a spacer unit. These results corroborate the experimental observations reported in the literature. The time-dependent density functional theory (TDDFT) calculations performed at the CPCM-CAM-B3LYP/6-31+G* level of theory showed better agreement with the experimental absorption spectra of some reported metal free organic dyes having silole in the spacer group compared to other functionals and are employed in this study. Indoline donor based dye 5 showed a much shorter absorption spectrum (absorption peak at 425 nm) and smaller electron injection driving force (Delta G(injection) = -1.77 eV) than the corresponding dye 8 containing silicon substituted indoline as a donor and a silole group as a spacer unit. lambda(max) = 502 nm and Delta G(injection) = -1.82 eV calculated for dye 8 are much larger than the corresponding silicon free dye 5. The silicon based dye 8 helps in achieving a much lower DGregeneration value than 5, which can facilitate the faster electron injection rate from the dye to the semiconductor TiO2. Dye 8 should also have a higher V-oc value compared to other dyes (5-7) due to favourable interaction with the electrolyte (I-/I-3(-)). The higher planarity and better conjugation in dye 8 facilitate the transfer of electrons from the dye molecules to the semiconductor TiO2. The calculations performed with phenyl protecting groups near the silicon center of the dye molecule 8 to diminish the dimerization process showed very similar optical properties as obtained with the corresponding unprotected dye system. The designed julolidine and pyrrolo-indolizine donor based dyes also showed a similar trend as observed for indoline donor based dyes.

Specific reagent for Cr(III): imaging cellular uptake of Cr(III) in Hct116 cells and theoretical rationalization - Ali, Firoj; Saha, Sukdeb; Maity, Arunava; Taye, Nandaraj; Si, Mrinal Kanti; Suresh, E.; Ganguly, Bishwajit; Chattopadhyay, Samit; Das, Amitava (Journal of Physical Chemistry B, 2015)
A new rhodamine-based reagent (L-1), trapped inside the micellar structure of biologically benign Triton-X 100, could be used for specific recognition of Cr(III) in aqueous buffer medium having physiological pH. This visible light excitable reagent on selective binding to Cr(III) resulted in a strong fluorescence turn-on response with a maximum at similar to 583 nm and tail of that luminescence band extended until 650 nm, an optical response that is desired for avoiding the cellular autofluorescence. Interference studies confirm that other metal ions do not interfere with the detection process of Cr(III) in aqueous buffer medium having pH 7.2. To examine the nature of binding of Cr(III) to L-1, various spectroscopic studies are performed with the model reagent L-1 which tend to support Cr(III)-eta(2)-olefin pi-interactions involving two olefin bonds in molecular probe L-1. Computational studies are also performed with another model reagent L-M to examine the possibility of such Cr(III)-eta(2)-olefin pi-interactions. Presumably, polar functional groups of the model reagent L-M upon coordination to the Cr(III) center effectively reduce the formal charge on the metal ion and this is further substantiated by results of the theoretical studies. This assembly is found to be cell membrane permeable and shows insignificant toxicity toward live colon cancer cells (Hct116). Confocal laser scanning microscopic studies further revealed that the reagent L-1 could be used as an imaging reagent for detection of cellular uptake of Cr(III) in pure aqueous buffer medium by Hct116 cells. Examples of a specific reagent for paramagnetic Cr(III) with luminescence ON response are scanty in the contemporary literature. This ligand design helped us in achieving the turn on response by utilizing the conversion from spirolactam to an acyclic xanthene form on coordination to Cr(III).

Does the position of the electron-donating nitrogen atom in the ring system influence the efficiency of a dye-sensitized solar cell? A computational study - Biswas, Abul Kalam; Barik, Sunirmal; Das, Amitava; Ganguly, Bishwajit (Journal of Molecular Modeling, 2016)
We have reported a number of new metal-free organic dyes (2-6) that have cyclic asymmetric benzotripyrrole derivatives as donor groups with peripheral nitrogen atoms in the ring, fluorine and thiophene groups as pi-spacers, and a cyanoacrylic acid acceptor group. Density functional theory (DFT) and time-dependent DFT (TD-DFT) calculations were employed to examine the influence of the position of the donor nitrogen atom and pi-conjugation on solar cell performance. The calculated electron-injection driving force (Delta G(inject)), electron-regeneration driving force (Delta G(regen)), light-harvesting efficiency (LHE), dipole moment (mu(normal)), and number of electrons transferred (Delta q) indicate that dyes 3, 4, and 6 have significantly higher efficiencies than reference dye 1, which exhibits high efficiency. We also extended our comparison to some other reported dyes, 7-9, which have a donor nitrogen atom in the middle of the ring system. The computed results suggest that dye 6 possesses a higher incident photon to current conversion efficiency (IPCE) than reported dyes 7-9. Thus, the use of donor groups with peripheral nitrogen atoms appears to lead to more efficient dyes than those in which the nitrogen atom is present in the middle of the donor ring system.
Keywords: DFT; Dye-sensitized solar cells; Organic dyes; Position effect; TD-DFT

Switch-on NIR probe for specific detection of Hg2+ ion in aqueous medium and in mitochondria - Agarwalla, Hrideshg; Mahajan, Pankaj S.; Sahu, Debashis; Taye, Nandaraj; Ganguly, Bishwajit; Mhaske, Santosh B.; Chattopadhyay, Samit; Das, Amitava (Inorganic Chemistry, 2016)
A new 4,4-difluoro-4-bora-3a,4a-diaza-s-indacene (BODIPY)-based probe molecule (L) is synthesized for specific binding to Hg2+ ion in physiological condition with an associated luminescence ON response in the near-IR region of the spectrum. Appropriate functionalization in the 5-position of each of two pyrrole moieties with styryl functionality in a BODIPY core helped us in achieving the extended conjugation and a facile intramolecular charge transfer transition with a narrow energy gap for frontier orbitals. This accounted for a poor emission quantum yield for the probe molecule L. Binding to. Hg2+ helped in interrupting the facile intramolecular charge transfer (ICT) process that was initially operational for L. This resulted in a hypsochromic shift of absorption band and a turn-on luminescence response with lambda(Em)(max) of 650 nm on specific binding to Hg2+. Observed spectral changes are rationalized based on quantum chemical calculations. Interestingly, this reagent is found to be localized preferentially in the mitochondria of the live human colon cancer (Hct116) cells. Mitochondria is one of the major targets for localization of He2+, which actually decreases the mitochondrial membrane potential and modifies various proteins having sulfudryl functionality(ies) to cause cell apoptosis. Considering these, ability of the present reagent to specifically recognize Hg2+] in the mitochondrial region of the live Hct116 cells has significance.

Fluorescent chemodosimeter for quantification of Cystathionine-y-synthase activity in plant extracts and imaging of endogenous biothiols - Agarwalla, Hridesh; Hoskere, Anila A.; Ali, Firoj; Pradhan, Swaraj Rashmi; Ganguly, Bishwajit; Pramanik, Sumit kumar; Das, Amitava (Chemical Communications, 2018)
A new reagent for quantification of CgS in plant extracts using a generalized methodology suitable for recognition of homocysteine (Hcy) with luminescence ON response.

Impact of half-crown/two carbonyl:-Ca2+ metal ion interactions of a low molecular weight gelator (LMWG) on its fiber to nanosphere morphology transformation with a gel-to-sol phase transition - Maity, Arunava; Dey, Ananta; Si, Mrinal Kanti; Ganguly, Bishwajit; Das, Amitava (Soft Matter, 2018)
We report here a smart functional low molecular weight gelator (LMWG) L, containing an unusual metal ion coordination site, i.e. ``half-crown/two carbonyl''. The gelator L shows excellent gelation behavior with typical fibrillar morphology in acetonitrile, methanol and ethanol media. Upon Ca2+ ion binding with its ``half-crown/two carbonyl'' coordination site, the acetonitrile gel of L exhibits a fiber to nanosphere morphology transformation along with a gel-to-sol phase transition as confirmed by microscopic investigation and by direct naked eye visualization, respectively. The mechanism involved in this morphology transformation and gel-to-sol phase transition process was studied thoroughly with the help of computational calculations and various spectroscopic experiments and discussed.